Prevalence, clinical characteristics, and biological markers of postmenopausal osteoporosis and knee osteoarthritis in Beijing: study protocol for a cross-sectional and prospective study - Lu, Zhenkai; Feng, Wenye; Wang, Yaxing; Zhang, Xuming; Wei, Xu; Chen, Ming; Wang, Shangquan; Cheng, Ting; Cui, Xin; Xie, Yanming (Frontiers in Medicine, 2025)
BackgroundPostmenopausal osteoporosis (PMOP) and knee osteoarthritis (KOA) are common musculoskeletal disorders that share risk factors such as aging, hormonal changes, and inflammation. PMOP often remains asymptomatic until fractures occur, while KOA leads to pain and disability. Their comorbidity remains underexplored, particularly in community settings. This study aims to investigate the prevalence, risk factors, and clinical features of PMOP-KOA comorbidity among Beijing residents aged 45–80 years, providing evidence-based recommendations for early identification, prevention, and management.MethodsOver 2 years, this study will conduct a PMOP-KOA screening and prospective follow-up in the Beijing community to investigate the incidence, risk factors, and clinical characteristics of PMOP-KOA. This study will undertake bone mineral density detection, collect biological samples, and record information via questionnaires.DiscussionThe study aims to investigate the incidence, risk factors, and clinical characteristics of PMOP-KOA comorbidity and explore related traditional Chinese medicine syndromes based on large community-based samples in Beijing. Data on PMOP-KOA occurrence and associated risk factors over the 2 years follow-up will be available on the Chinese Clinical Trial Registry (ChiCTR2300073575).